2014
DOI: 10.1039/c3ib40230d
|View full text |Cite
|
Sign up to set email alerts
|

The contractile strength of vascular smooth muscle myocytes is shape dependent

Abstract: Vascular smooth muscle cells in muscular arteries are more elongated than those in elastic arteries. Previously, we reported changes in the contractility of engineered vascular smooth muscle tissue that appeared to be correlated with the shape of the constituent cells, supporting the commonly held belief that elongated muscle geometry may allow for the better contractile tone modulation required in response to changes in blood flow and pressure. To test this hypothesis more rigorously, we developed an in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 81 publications
5
41
0
1
Order By: Relevance
“…2A). Quantification of actin alignment using a previously developed technique 14a revealed alignment to be statistically higher (p<0.05) at an AR of 1:7 compared to 1:5 and 1:3 (Fig. 2C).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…2A). Quantification of actin alignment using a previously developed technique 14a revealed alignment to be statistically higher (p<0.05) at an AR of 1:7 compared to 1:5 and 1:3 (Fig. 2C).…”
Section: Resultsmentioning
confidence: 94%
“…14 We therefore evaluated whether altered VIC shape resulted in changes in cytoskeletal and nuclear architecture. Phalloidin staining of F-actin, showed that the filaments became more prominent and aligned along the longitudinal direction of the cell as AR increased (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The functionality of iSMC was also evaluated by traction force microscopy 35,36 . We compared the traction forces produced in control EPC and iSMC (4 weeks).…”
Section: Resultsmentioning
confidence: 99%
“…Cell elongation influences the behavior of many cell types, particularly myocytes, which rely on their shape for directional force generation. 18-20 While the function of macrophages in the body is quite different, these cells have been shown to exhibit different shapes in vivo, where M2 polarized cells are more elongated and often found within fibrous tissue architectures. 21-23 Immune cells may in fact share similar mechanisms with other cell types for sensing their extracellular environment.…”
Section: Introductionmentioning
confidence: 99%